Effect of Application of Rock Phosphate on Soil P Adsorption and Fractionation at Dystrudepts of Cibatok, Bogor - Dedi NURSYAMSI; L. ANGGRIA; . NURJAYA (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2011)
Phosphorous fertilization in both lowland and upland is an activity that must be done to increase agricultural production in Indonesia. Farmers typically use an acidulated rock phosphate, such as: TSP, SP-36, or SP-18 where its effectiveness varies depending on the type of soil and cultivated crops. Rock phosphate fertilizers have a high prospect to be used directly inacid upland soils because of its effectiveness equals the acidulated rock phosphate but the price is cheaper. Laboratory experiments aimed at studying the effect of the rock phosphate application on soil P adsorption and fractionation as well as determining the critical level of soil P for maize P-12 variety growth have been carried out using soil samples taken from rock phosphate fertilization experiment in the field, at volcanic Dystrudepts soil in Cibatok, Bogor. Analysis for soil P adsorption Fox and Kamprath (1970) methods were used, while its fractionation used modified Sekiya (1983) methods. The results showed that the use of rock phosphate increased soil soluble P therefore its availability for plant growth increased too. Beside that, it increased all soil P forms as well as soil HCl-P and Bray I-P significantly. P forms in tested soil from high to low were the residual-P > organic-P > Fe-P > Al-P > Ca-P in which the form of residual-P, Fe-P, and total-P played an important role in controlling the availability of soil P. Critical level of soil Fe-P, residual-P, and total-P for maize P-12 variety growth in the soil were 320, 510, and 1,250 mg P2O5 kg-1 respectively.